Pengaruh Pembiayaan Mudharabah, Pembiayaan Musyarakah dan Non-Performing Financing Terhadap Profitabilitas - Ulya, Eva Suci Zulfatul; Sadiyah, Mahmudatus (Jurnal Iqtisaduna, 2025)
This study aims to analyze the influence of mudharabah financing, musyarakah financing, and Non-Performing Financing (NPF) on the profitability of Islamic commercial banks in Indonesia in the 2019-2023 period, as measured by Return on Assets (ROA). The research method uses panel data regression analysis with secondary data from 6 Islamic commercial banks registered with the Financial Services Authority (OJK), which were selected through purposive sampling technique based on certain criteria. Data processing is done using EViews 10 software, the data analysis process includes descriptive statistical analysis, classical assumption testing, and hypothesis testing. The results showed that mudharabah financing has no significant effect on ROA, while musyarakah financing has a positive and significant effect. NPF has a significant negative effect on ROA, indicating that the high risk of non-performing financing can reduce bank profitability. The results of this research emphasise the need for more focused risk mitigation strategies and the development of more adaptive financing products so that Islamic banks can increase their profitability in the future, especially in the face of unforeseen economic challenges.